From Uber to Local Commuting Platforms: The Unrevealed Diversity of Small and Medium Platform Initiatives. Case Study of the Mobility Sector in France - Mathilde Abel (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2020)
In January 2019, Amazon Inc. became the first market capitalization on the New York Stock Exchange, ahead of Microsoft Corporation. For the first time a marketplace –a digital platform–was taking the lead before traditional companies from the digital economy sector. Two weeks later, Uber reported a net loss of 865 million dollars in the fourth quarter of 2018. Digital platforms, as new intermediaries, are shaping the functioning rules of this (new) market economy (sometimes called “platform capitalism” (Srnicek, 2018) and challenge economics methods. Since Rochet and Tirole’s (2003) pioneer research in industrial economics on two-sided and multisided markets, platforms have been the subject of much research in economics and management.Whether it is to build typologies, or to analyze the emergence of the diverse business models or the reconfiguration of value chains and their socio-economic impacts, these approaches acknowledge the existence of massive disruptive effects, related to the dissemination of digital platforms. The results are new forms of economic activity organization, far from the classical theoretical representations of the industry, particularly regarding the identities and behaviors of the economic actors involved in these activities. This study is on mobility platforms in France, with a focus on the price-fixing process, highlights the shortcomings of approaches that tend to conceive platforms as ecosystems. It reveals the great diversity that exists and stressing the need of new economic tools to build a power relations analysis.